Identification of Supply Chain Performance Indicators: Case Study of Costa Rican Coffee Production - Montero Vega, Mercedes (2018)
Background: coffee production is one of the most important agricultural products for Costa Rica, especially because of the large proportion of small and medium farmers involved. This research intends to provide the identification of performance indicators for coffee production using the Asociación de Productores Agropecuarios de las Comunidades de Acosta y Aserrí (ASOPROAAA), as case of study. Methods: 21 expert surveys were conducted, based on ASOPROAAA and its farmers. Results: indicators of performance were measured in each of the sustainability dimensions. Farmers’ record keeping was a problem; however, data was collected and double checked by participants. Conclusion: the identification of supply chain performance indicators was possible in all the sustainability dimensions, benchmarking of these results with other Costa Rican companies would require further research. The identified indicators can be used as a first approach for sustainable performance in coffee, since they were adapted to the production system and its specific characteristic.